Feature articles : discovering Davies-land : Arthur B. Davies in the West, 1905 - Eldredge, Charles C (American art, 2017)
Arthur Davies's 1905 excursion in the West is only occasionally mentioned in discussions of his career, and then but briefly. The artist's itinerary and the subjects that captured his attention have, like his western sketches, been largely neglected. Scant written records from his travels and the scattering of the more than seventy oil sketches produced en route contribute to this neglect. Yet in the years after his return, the subjects and compositions of Davies's easel paintings suggest the impact that unique trip to the American West had for this otherwise dedicated Europhile. Discovery of a number of the small oil-on-panel sketches helps to identify the path Davies pursued. More importantly, the sketches suggest the inspiration for his post-excursion canvases, many of which grew larger in format in response to the scale of the spacious western landscape. A good number of these larger paintings were in fact landscapes, a motif otherwise relatively rare among Davies's oils, and incorporated familiar aspects of western scenery (mountain horizons, towering redwoods). Some also included nude figures in newly sensual poses and combinations. [Abridged Publication Abstract]